An application of a reliability based method to evaluate open pit slope stability - Valerio, M.; Clayton, C.; D.’Ambra, S.; Yan, C. (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
The stability of open pit rock slopes is commonly assessed using deterministic methods. A single value for the Factor of Safety of the slope is calculated, and is assumed to represent the overall stability of the slope. A limitation of the deterministic approach is that it does not account for the natural variability of the input parameters or the uncertainty caused by sampling. The uncertainty and variability of input parameters such as frictional strength, cohesive strength, and discontinuity orientations are often accounted for by selecting values that incorporate conservatism based on limited laboratory testing or other data collection methods. The confidence in the Factor of Safety calculated using deterministic analyses remains a matter of engineering and experiential judgment.